Epidemiological evidence for a hereditary contribution to myasthenia gravis: a retrospective cohort study of patients from North America - Joel Oger; Joshua D Green; Bryan J Traynor; Richard J Barohn; Michael Benatar; Emanuela Bartoccion; Derrick Blackmore; Vinay Chaudhry; Manisha Chopra; Andrea Corse; Mazen M Dimachkie; Amelia Evoli; et al. (BMJ Open)
Objectives To approximate the rate of familial myasthenia gravis and the coexistence of other autoimmune disorders in the patients and their families.Design Retrospective cohort study.Setting Clinics across North America.Participants The study included 1032 patients diagnosed with acetylcholine receptor antibody (AChR)-positive myasthenia gravis.Methods Phenotype information of 1032 patients diagnosed with AChR-positive myasthenia gravis was obtained from clinics at 14 centres across North America between January 2010 and January 2011. A critical review of the epidemiological literature on the familial rate of myasthenia gravis was also performed.Results Among 1032 patients, 58 (5.6%) reported a family history of myasthenia gravis. A history of autoimmune diseases was present in 26.6% of patients and in 28.4% of their family members.Discussion The familial rate of myasthenia gravis was higher than would be expected for a sporadic disease. Furthermore, a high proportion of patients had a personal or family history of autoimmune disease. Taken together, these findings suggest a genetic contribution to the pathogenesis of myasthenia gravis.